Evaluation of papillo-incisal distance in different arch forms and with different shapes of incisive papilla in Moradabad population - A descriptive study - Samarth Kumar Agrawal; Romil Singhal; Shradha Pagia; Kumari Kalpana (Journal of Dental Problems and Solutions - Peertechz Publications, 2021)
Error in placement of maxillary anterior teeth in complete denture contributes to artificial senile appearance, thus not satisfying the aesthetic values that patient deserves.  Material and Method: A total of 249 patients were selected between 17-40 years of age. Patients had normal dentition, well aligned arches with all teeth present. Arch form was assessed by using 3M Unite template. Shape of incisive papilla was marked on cast. Measurement of horizontal distance between posterior border of incisive papilla and labial surface of maxillary central incisor was done with digital vernier caliper. Result: Square form had minimum mean distance (11.76+1.59 mm). Tapered form had maximum mean distance (12.43=1.74 mm). For ovoid form, the mean distance was 12.19+1.24 mm. Overall, cylindrical shape was the most common (34.1%) followed by pear (26.5%), flame (20.1%) and dumbel or round shape (6% each). Statistical evaluation revealed that there was no significant difference among different arch forms with respect to shape of incisive papilla.  Conclusion: Distance between incisive papilla and maxillary central incisor is independent of arch form and shape of Incisive papilla.